LearnChain: Building the next-generation of the Knowledge-Based Economy - D’Césares, Isaac; Campos, Maria Luiza Machado; Cruz, Sérgio Manuel Serra da (Anais do Colóquio em Blockchain e Web Descentralizada (CBlockchain); 2024: Anais do II Colóquio em Blockchain e Web DescentralizadaDO - 10.5753/cblockchain.2024.3113, 2024)
This study addresses the challenges of the current knowledge economy, particularly in education, highlighting the limitations of centralized systems and monetization of educational Web systems. It introduces LearnChain, a blockchain-based solution promoting decentralization, transparency, incentivization, and privacy, aimed at offering equitable monetization for all stakeholders. The paper outlines the LearnChain architecture, unique features, and its blockchain foundation, concluding with its potential impacts and future research.